MENGAPA PERLU PENDIDIK DAN TENAGA KEPENDIDIKAN UNTUK PENDIDIKAN LUAR SEKOLAH (NONFORMAL) - Washington P Napitupulu (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
This paper discusses about the urgency of the provision of ‘nonformal educators and educational personnel’. Starting with a proposition that if formal education is already developed highly, then there will be no need for nonformal education programs, and consequently no need for nonformal educators and educational personnel. But, the real situations in the industrialized countries of USA and Japan are to the contrary. Nonformal education programs in those advanced countries have been developed and become part and parcel of learning-teaching societies. If the industrialized countries are still in need of nonformal education programs, then the need is indeed more urgent in developing countries, such as Indonesia, including the provision of nonformal educators and educational personnel, but of course not the same qualification as that for ‘formal educators and educational personnel’. The paper would like that Indonesian education goes back to the ideas of three interrelated centers of education, i.e. (a) family education, (b) school education, and (c) community education, and away from the present push toward too much school-oriented education. The responsibility of character-building of the young generation should stay in the hands of parents (family education as the first and foremost center) and cannot be left to the school teachers alone.